Quality Improvement Management at State Elementary School 64 Prabumulih (Lembaga Pengembangan Kinerja Dosen, 2025)
The improvement of education quality has become a major challenge in modern education, where elementary schools are required to continuously adapt to the developmental needs of students and societal demands. This study aims to describe and analyze the management strategies for improving education quality at SD Negeri 64 Prabumulih, as well as to identify the supporting factors and obstacles influencing its implementation. The research method used is qualitative with a descriptive approach, employing data collection techniques such as in-depth interviews, observation, and document analysis. The results indicate that the management strategies implemented at SD Negeri 64 Prabumulih include participatory planning, teacher capacity building, resource optimization, and continuous evaluation. The main supporting factors for success are visionary school leadership, teacher commitment, and community support, while the challenges faced include limited infrastructure, a high administrative workload for teachers, and uneven parental involvement. This study provides an important contribution to enriching the understanding of the implementation of quality management in elementary schools with limited resources.